NATIONAL AND CULTURAL CODES AND GENDER REPRESENTATION IN TRADITIONALIST PROSE: CROSS-MEANINGS OF RUSSIAN AND UZBEK LITERATURES - Otabek Zhumaev (Modern American Journals, 2025)
The article examines national and cultural codes as fundamental elements of a literary text, in which collective values, historical memory and models of gender identity are fixed. Special attention is paid to how these codes function in the traditionalist prose of Russian and Uzbek literature, forming stable representations of the feminine and masculine principles. genre structures, but also in the deep cultural symbolism that replicates the images and roles enshrined in the historical tradition. The comparative approach makes it possible to identify the similarities and differences in the mechanisms of the formation of gender models in the literary consciousness of the two peoples, whose cultural systems developed in different religious, philosophical and social contexts. It is emphasized that traditionalism does not impede literary evolution, but, on the contrary, forms a platform for the renewal of national identity, while preserving stable semiotic markers. The study reveals the transformations taking place in the system of gender representation in the context of modernization and global cultural pressure, while demonstrating how national and cultural codes adapt without losing their deep connection with the past.
Keywords: National-cultural codes, gender representation, traditionalism, literary identity, Russian prose, Uzbek prose, cultural memory, artistic discourse, comparative analysis